Predictors of anastomotic leak and conduit necrosis after oesophagectomy: Results from the oesophago-gastric anastomosis audit (OGAA) - Griffiths, Ewen A (European journal of surgical oncology, 2024)
BACKGROUND: Both anastomotic leak (AL) and conduit necrosis (CN) after oesophagectomy are associated with high morbidity and mortality. Therefore, the identification of preoperative, modifiable risk factors is desirable. The aim of this study was to generate a risk scoring model for AL and CN after oesophagectomy. METHODS: Patients undergoing curative resection for oesophageal cancer were identified from the international Oesophagogastric Anastomosis Audit (OGAA) from April 2018-December 2018. Definitions for AL and CN were those set out by the Oesophageal Complications Consensus Group. Univariate and multivariate analyses were performed to identify risk factors for both AL and CN. A risk score was then produced for both AL and CN using the derivation set, then internally validated using the validation set. RESULTS: This study included 2247 oesophagectomies across 137 hospitals in 41 countries. The AL rate was 14.2% and CN rate was 2.7%. Preoperative factors that were independent predictors of AL were cardiovascular comorbidity and chronic obstructive pulmonary disease. The risk scoring model showed insufficient predictive ability in internal validation (area under the receiver-operating-characteristic curve [AUROC] = 0.618). Preoperative factors that were independent predictors of CN were: body mass index, Eastern Cooperative Oncology Group performance status, previous myocardial infarction and smoking history. These were converted into a risk-scoring model and internally validated using the validation set with an AUROC of 0.775. CONCLUSION: Despite a large dataset, AL proves difficult to predict using preoperative factors. The risk-scoring model for CN provides an internally validated tool to estimate a patient's risk preoperatively.
Keywords: ezofagektomie; netěsnost anastomózy; Esophagus; hodnocení rizik; ezofágus; Male; Risk Assessment; Risk Factors; ROC Curve; Esophageal Neoplasms; žaludek; Pulmonary Disease, Chronic Obstructive; Anastomotic Leak; Stomach; Aged; mužské pohlaví; senioři; nekróza; anastomóza chirurgická; nádory jícnu; Necrosis; lidé; ženské pohlaví; Esophagectomy; Humans; Body Mass Index; Anastomosis, Surgical; rizikové faktory; chronická obstrukční plicní nemoc; index tělesné hmotnosti; Female; ROC křivka; lidé středního věku; Middle Aged